Argumen Ayat-Ayat Politik Dalam Al Qur’an - Ahmad Ari Masyhuri; Chairun nisa; Moh Bakir (STAI Al-Mujtama Pamekasan, 2023)
Searching for political verses in the Qur'an is very important for the benefit of the ummah and guidelines for life in the nation and state, as human beings are actually created from different ethnic groups and religions, so this argument gives broad meaning in an academic perspective. The ability to present and understand every word of Allah requires the methodology of ulumul qur'an (Qur'anic sciences) which has been inherited by previous scholars, in the form of a set of interpretive tools that can reveal explicit and implicit messages, including verses of the Qur'an which has a political nature.The essence of politics (siyasiyah) in the perspective of the Qur'an implies the desire or way of Muslims to make Islamic teachings a curriculum of life (manhajul hayah). This is reflected in all life activities. This does not mean that the state must be based on the Koran, but that the values ​​of the Koran are reflected in life because the values ​​of the Koran are universal.Politics in the view of the Qur'an or Islamic politics (siyâsah islamiyah) aims to elevate the dignity, status and dignity of mankind to a more qualified and civilized direction according to their functions and duties as caliphs of Allah on earth, spreading mercy and peace and safety to all universe. Islamic politics is achieved if the perpetrators have morals, are moral, civilized, and are responsible to God and others. Keywords: politics, life curriculum, grace, responsibility